Cardio-Immunology of Myocarditis: Focus on Immune Mechanisms and Treatment Options - Maisch, Bernhard (Frontiers in Cardiovascular Medicine, 2019)
Myocarditis and inflammatory cardiomyopathy are syndromes, not aetiological disease entities. From animal models of cardiac inflammation we have detailed insight of the strain specific immune reactions based on the genetic background of the animal and the infectiosity of the virus. Innate and adaptive immunity also react in man. An aetiological diagnosis of a viral vs. a non-viral cause is possible by endomyocardial biopsy with histology, immunohistology and PCR for microbial agents. This review deals with the different etiologies of myocarditis and inflammatory cardiomyopathy on the basis of the genetic background and the predisposition for inflammation. It analyses the epidemiologic shift in cardiotropic viral agents in the last 30 years. Based on the understanding of the interaction between infection and the players of the innate and adaptive immune system it summarizes pathogenetic phases and clinical faces of myocarditis. It gives an up-to-date information on specific treatment options beyond symptomatic heart failure and antiarrhythmic therapy. Although inflammation can resolve spontaneously, specific treatment directed to the causative etiology is often required. For fulminant, acute, and chronic autoreactive myocarditis without viral persistence immunosuppressive treatment can be life-saving, for viral inflammatory cardiomyopathy ivIg treatment can resolve inflammation and often eradicate the virus.